Angiotensin II type 2 receptor mediates high fat diet-induced cardiomyocyte hypertrophy and hypercholesterolemia. (1st December 2019) - Lima, Vanessa M.; Lino, Caroline A.; Senger, Nathalia; de Oliveira Silva, Tábatha; Fonseca, Renata I.B.; Bader, Michael; Santos, Robson A.S.; Júnior, Jose Donato; Barreto-Chaves, Maria Luiza M.; Diniz, Gabriela P.
Abstract: Obesity is the major risk factor for several cardiovascular and metabolic disorders. Previous studies reported that deletion of Angiotensin II type 2 receptor (AT2R) protects against metabolic dysfunctions induced by high fat (HF) diet. However, the role of AT2R in obesity-induced cardiac hypertrophy remains unclear. Male AT2R knockout (AT2RKO) and wild type (AT2RWT) mice were fed with control or HF diet for 10 weeks. HF diet increased cardiac expression of AT2R in obese mice. Deletion of AT2R did not affect body weight gain, glucose intolerance and fat mass gain induced by HF feeding. However, loss of AT2R prevented HF diet-induced hypercholesterolemia and cardiac remodeling. Mechanistically, we found that pharmacological inhibition or knockdown of AT2R prevented leptin-induced cardiomyocyte hypertrophy in vitro . Collectively, our results suggest that AT2R is involved in obesity-induced cardiac hypertrophy. Highlights: Cardiac expression of AT2R is increased in obese mice. Loss of AT2R prevented high fat diet-induced hypercholesterolemia. Loss of AT2R prevented high fat diet-induced cardiac remodeling. Pharmacological blockage or knockdown of AT2R abolished leptin-induced cardiomyocyte hypertrophy in vitro .